2022
DOI: 10.3389/fcvm.2022.928782
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness, Biomarkers of Liver Fat, and the Development of Metabolic Dysfunction in Metabolically Healthy Population: A Prospective Study

Abstract: BackgroundMetabolic dysfunction is known to be associated with arterial stiffness. However, the risks of metabolic syndrome and diabetes due to arterial stiffness and the potential mechanism remain unclear. We aimed to investigate the association of arterial stiffness with the risk of metabolic syndrome and diabetes, and determine whether this association is mediated by liver fat.MethodsA prospective study was conducted with 4,139 Chinese adults who were metabolically healthy at baseline. Arterial stiffness wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(42 reference statements)
2
3
0
Order By: Relevance
“…Our finding of elevated arterial stiffness in PWV in both the CWO and T2D groups when compared with reference control agrees with previous work finding decreased distensibility as a marker of stiffness in both the ascending and descending aorta of people with T2D and obesity [37,42]. We speculate that the greater aortic stiffness in people with relatively uncomplicated T2D and obesity is an initial marker of vascular disease in this population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding of elevated arterial stiffness in PWV in both the CWO and T2D groups when compared with reference control agrees with previous work finding decreased distensibility as a marker of stiffness in both the ascending and descending aorta of people with T2D and obesity [37,42]. We speculate that the greater aortic stiffness in people with relatively uncomplicated T2D and obesity is an initial marker of vascular disease in this population.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent report of individuals with heart failure with preserved ejection fraction, arterial stiffness correlated with visceral adipose tissue, consistent with our observations with obesity alone [36]. A Chinese population study reported similar associations between arterial stiffness measured by brachial–ankle PWV and obesity [37]. Arterial stiffness as measured by 2D QA PC-MRI PWV in T2D and CWO significantly differed between the two study groups only in the ascending aorta.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The participants were from an ongoing cohort study in Jiading District, Shanghai, China. The study design and detailed methods have been described previously 8,9 . Briefly, registered residents from two communities in Jiading District were invited to attend a comprehensive health examination, and 10 375 residents aged 40 years or older were recruited between March and August 2010.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and detailed methods have been described previously. 8 , 9 Briefly, registered residents from two communities in Jiading District were invited to attend a comprehensive health examination, and 10 375 residents aged 40 years or older were recruited between March and August 2010. All the participants completed a standard questionnaire and a set of clinical measurements.…”
Section: Methodsmentioning
confidence: 99%